Research and Development on Android Application-Based Education for Self-Care Management in Type 2 Diabetes Patients - Yusuf Efendi; Defri Pria Wicaksana; Mohamad Roni Alfaqih (Indonesian Journal of Global Health Research, 2025)
Diabetes Mellitus type 2 is a chronic disease that requires long-term management, including the patient's ability to perform self-care independently. This study aims to develop an Android-based application that can help type 2 DM patients in carrying out self-care activities, such as regulating diet, monitoring blood sugar levels, physical activity, and managing medicatio.. This research aims to develop an Android-based application for DM patients type 2 as a promotive and rehabilitative effort. Methods: The research design used is research and development (R&D) with a descriptive analysis approach. The application development process follows the stages of the system development model which includes needs analysis, design, implementation, and evaluation. The data collection method used is primary data, secondary data, interviews and questionnaires to type 2 DM patients and health workers to identify user needs. The Pearson Product Moment correlation technique has been used to examine the validity of 25 questionnaire items with 30 respondents, covering program usability, interface display, convenience of use, and educational benefits. Cronbach's Alpha was used for the reliability test, and the result was 0.87 (reliable). Inclusion Inclusion criteria included type 2 DM patients and health workers (nurses) at Bojonegoro Hospital. Three steps were taken in the data analysis process for this study: data reduction, data display, and data verification. Results The development results show that the application created can be well received by users, and is considered useful in improving patient understanding and skills in carrying out self-care independently. Conclusion: The development of an Android-based application for self-care in patients with Diabetes Mellitus type 2 has been successfully carried out with the aim of increasing patient awareness, knowledge, and compliance with self-management of their disease. This application provides various educational and interactive features such as recording blood sugar levels, medication reminders, healthy diet guidelines, recommended physical activities, and educational materials about diabetes mellitus type 2. This application is expected to be one of the alternative technology-based solutions in supporting chronic disease management, especially Diabetes Mellitus type 2.